Determining the Site of Action of Strigolactones during Nodulation. Issue 1 (27th July 2017) - McAdam, Erin L.; Hugill, Cassandra; Fort, Sebastien; Samain, Eric; Cottaz, Sylvain; Davies, Noel W.; Reid, James B.; Foo, Eloise
Abstract : The plant hormone strigolactone promotes infection thread formation but does not appear to influence other stages of nodulation, including nitrogen fixation. Abstract: Strigolactones (SL s) influence the ability of legumes to associate with nitrogen-fixing bacteria. In this study, we determine the precise stage at which SL s influence nodulation. We show that SL s promote infection thread formation, as a null SL -deficient pea ( Pisum sativum ) mutant forms significantly fewer infection threads than wild-type plants, and this reduction can be overcome by the application of the synthetic SL GR24. We found no evidence that SL s influence physical events in the plant before or after infection thread formation, since SL -deficient plants displayed a similar ability to induce root hair curling in response to rhizobia or Nod lipochitooligosaccharides (LCO s) and SL -deficient nodules appear to fix nitrogen at a similar rate to those of wild-type plants. In contrast, an SL receptor mutant displayed no decrease in infection thread formation or nodule number, suggesting that SL deficiency may influence the bacterial partner. We found that this influence of SL deficiency was not due to altered flavonoid exudation or the ability of root exudates to stimulate bacterial growth. The influence of SL deficiency on infection thread formation was accompanied by reduced expression of some early nodulation genes. Importantly, SL synthesis is down-regulated by mutations in genes of the Nod LCO signaling pathway, and this requires the downstream transcription factor NSP2 but not NIN . This, together with the fact that the expression of certain SL biosynthesis genes can be elevated in response to rhizobia/Nod LCO s, suggests that Nod LCO s may induce SL biosynthesis. SL s appear to influence nodulation independently of ethylene action, as SL -deficient and ethylene-insensitive double mutant plants display essentially additive phenotypes, and we found no evidence that SL s influence ethylene synthesis or vice versa.